1980
DOI: 10.1016/0092-8674(80)90134-8
|View full text |Cite
|
Sign up to set email alerts
|

Unique mode of transcription in vitro by vesicular stomatitis virus

Abstract: In addition to the five mRNA species and 47 nucleotide long leader RNA synthesized by purified virions of vesicular stomatitis virus, at least three discrete low molecular weight RNA species having approximate chain lengths of 28, 42 and 70 nucleotides can be detected in vitro. Each of these RNA species displays a unique and characteristic T1 fingerprint profile and contains (p)ppAA as its 5' terminus. By partial sequence analyses, two of the small RNA products, 42 and 28 bases long, were found to contain 5' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

1981
1981
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 23 publications
3
95
1
Order By: Relevance
“…Several models were proposed for this sequential mode of VSV mRNA transcription in vitro (Banerjee et al, 1977). Some recent observations have suggested a model (Testa et al, 1980) in which the transcriptase is located at putative multiple promoter sites on the template RNP and initiates RNA chains. RNA chain elongation, however, occurs only after its T-proximal gene is transcribed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several models were proposed for this sequential mode of VSV mRNA transcription in vitro (Banerjee et al, 1977). Some recent observations have suggested a model (Testa et al, 1980) in which the transcriptase is located at putative multiple promoter sites on the template RNP and initiates RNA chains. RNA chain elongation, however, occurs only after its T-proximal gene is transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…Each RNA species was eluted from the gel, quantified, and identified by fingerprint analyses. The bands designated leader RNA, RNA I and RNA III were confirmed to be leader RNA, small initiated N mRNA and NS mRNA, respectively, as described previously (Testa et al, 1980). RNA II was confirmed to be the G-start RNA species of 28 bases, synthesized within the N gene as observed by Schubert et al (1982) and RNA IV, which is a mixture of three distinct bands, was confirmed to be the initiated N mRNA sequence of chain lengths 11 to 14 as previously observed by Pinney & Emerson (1982a) (data not shown).…”
Section: Short Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of how NS mRNA transcription starts are not known, that is whether the new RNA is generated by a nucleolytic processing event, a stop/start reinitiation, or an initiation by a separate polymerase molecule. No one current model satisfactorily encompasses all observations (Ball & White, 1976;Herman et al, 1978;Testa et al, 1980). We do know the start position of the new mRNA, and that it is capped and methylated by some part of the virus's transcription apparatus.…”
Section: Vesicular Stomatitis Virusmentioning
confidence: 99%